Sistem Pendukung Keputusan Smart Leasing Value Asset dengan Perhitungan NPV dan NAL Berbasis Website - Febry P J Sibuea; Astriyani Sandya Paramita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The process of evaluating the feasibility of asset financing in business organizations is often carried out manually, making it prone to calculation errors, data inconsistencies, and delays in decision-making. This condition creates the need for a system capable of providing structured and objective analysis, particularly in determining whether an asset is more feasible to buy or lease. This study aims to develop a Smart Leasing Value Asset Decision Support System that integrates two financial analysis methods: Net Present Value (NPV) to calculate the present value of future cash flows and Net Advantage to Lease (NAL) to compare the economic benefits of purchasing and leasing an asset. The development method used is Rapid Application Development, which allows for rapid system development through a prototype approach and active user involvement. The implementation results show that the tested asset has a positive NPV value, thus being considered feasible, while a negative NAL value indicates that the purchase option is more profitable than leasing. These findings prove that the system is capable of producing accurate calculations, consistent with manual calculations, and effective in improving the speed and quality of decision-making. This system has the potential for further development by adding sensitivity analysis and real-time financial data integration.